The impact of a primary school reform on educational stratification : a Norwegian study of neighbour and school mate correlations - Oddbjørn Raaum; Kjell G. Salvanes; Erik Ø. Sørensen (Institute for the Study of Labor (IZA), 2003)
School quality is hard to define and measure. It is influenced by not only school expenditures, but also characteristics that are hard to measure like norms and peer effects among teachers and pupils. Furthermore, family background and community characteristics are important in explaining educational outcomes. In this paper we study the composite effect of primary schools and neighbourhoods on adult educational attainment controlling for family characteristics. Instead of identifying the effect of specific neighbourhood and school characteristics on educational attainment, we focus on correlations in final years of schooling among neighbouring children and school mates. We find a clear trend of declining influence of childhood location over the 24 year period (birth cohorts 1947-1970). Then we ask whether a change in the compulsory school law extending the mandatory years of education, can explain this pattern. We find some effect of the primary school reform on the change in the neighbourhood effect. Motivated by the fact that neighbouring children typically go to the same school, we estimate school mate correlations for children born in the 1960s. The overall impact of factors shared by children who graduated from the same school at the age of 15/16 is negligible. The variation in ?school quality? and the impact of peers on final educational attainment seem to have been very limited in Norway.
Keywords: I21; R23; J13; 330; families; neighbours; schools; educational reforms; peer-effects; Bildungsniveau; Familie; Wohnstandort; Bildungsreform; Allgemeinbildende Schule; Norwegen